Administrative Evolution of the Punjab and British Rule (1849-1859): The Administrative Evolution of the Punjab under British Rule (1849-1859) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
After annexing the Punjab to the British Empire on March 29, 1849, the Governor General, Lord Dalhousie's next task was to decide as to what form of administration would be best suited to this newly occupied province. Charles Gough, the British Commander-in-Chief, suggested that the Punjab, like Sind, should have a military rule. Other Senior Officers were of the view that like the other provinces of India, it should be ruled by civilians. Dalhousie decided to combine the two systems by setting up a civil administration in the Punjab manned by both. He established Board of Administration with Henry as President and two other members, John and Mansel as his colleagues on an equal footing. To each member of the Board was assigned a task, suited to his aptitude and favourable to his genius. According to Willam Kay the members of the board were certainly different but their responsibility was common. Every member was responsible for proceedings of other members. Documents of every problem went to the each member. He wrote his views on it and it came to the board, and some decision was taken jointly. This board worked from 1849 to 1853 A.D. for about four years. The board accomplished the work of transition from the Sikh to the British rule. The people of the Punjab had gradually accepted themselves to the new order of things. The Board of Administration was abolished in 1853 A.D., and the Punjab was made a Chief Commissioner's province. Thus, Punjab was administered by three commissioners again-(i) Chief Commissioner (ii) Judicial Commissioners (iii) Financial Commissioner. They were John's assistant and not his colleagues in any sense. John gave such peace and prosperity to the people as had never been known in the province within the living memory of man. By 1857, he had perfected the Machinery of every department and won over the martial people of the Punjab to such an extent that the province remained loyal during the fateful days of the Muting for them.